Investigation of dynamic models of independently rotating wheels of wagons - Bureika, Gintautas; Lingaitis, Leonas P.; Mikaliūnas, Šarūnas (Transport, 2004)
The article deals with the modelling of independently rotating wheels (IRW) systems for wagons. The research work of the intensity of rolling stock wheels rims and flanges is observed. The main performance objectives of IRW are to reduce winding of wheel‐sets, to enable railway rolling stocks to achieve higher speeds, to decrease wear of rail and wheel rolling surface, to improve the performance on railway curves and to reduce lateral displacement on rails. IRW with profiled tread are examined and the mathematical model of these IRW is created. Finally, the peculiarities of the stability and wearing characteristics of such IRW systems are presented.First Published Online: 27 Oct 2010